The Blalock-Taussig Shunt - Yuan, Shi-Min; Shinfeld, Amihay; Raanani, Ehud (Journal of cardiac surgery, 2009)
Background and aim of the study: Even though the Blalock‐Taussig (B‐T) shunt, either classic or modified, has been advocated and successfully employed in clinical practice for more than half a century, a systemic review on this procedure is still scanty. This warrants us a zest in making a comprehensive survey on this subject. Methods: Articles were extensively retrieved from the MEDLINE database of National Library of Medicine USA if the contained information relevant to the B‐T shunt in terms of the conduit options, modified surgical techniques, surgical indications, short‐ and long‐term results, complications, and prognosis. Further retrieval was undertaken by manually searching the reference list of relevant papers. Results: Classical or modified B‐T shunts, either on ipsilateral or contralateral side to the aortic arch, can be performed on patients of any age with minimum postoperative complications and low operative mortality. Expended polytetrafluoroethylene has gained satisfactory long‐term patency rate in the construction of the modified B‐T shunt. Excellent pulmonary artery growth was observed in the patients with a modified B‐T shunt, and it has shown superb prognosis over the classic with regard to hemodynamics, patency rate, and survival. Conclusions: The modified B‐T shunt that was developed on basis of the classic fashion remains the preferable palliative procedure aiming at enhancing pulmonary blood flow for neonates and infants with complicated cyanotic congenital heart defects. The modified B‐T shunt is technically simpler with less dissection, and blood flow to the respective arm is not jeopardized. It has been proved to be of low risk, excellent palliation, and is associated with excellent pulmonary artery growth, has become the most effective palliative shunt procedure of today.